Jual Beli dengan Klausula Baku dalam Perspektif Kompilasi Hukum Ekonomi Islam - Saifullah; Hilda (Mu’amalah: Jurnal Hukum Ekonomi Syariah, 2022)
This study examines the use of standard clauses (klausula baku) in contracts, which often create an imbalance by allowing the stronger party to dictate terms, leaving the weaker party with no opportunity for negotiation. This practice can lead to unfair transactions, especially when the weaker party lacks bargaining power or knowledge. The research explores how Islamic law views such practices and their impact on fairness and transparency in commercial transactions. The gap in existing literature lies in the limited analysis of how klausula baku contradicts Islamic principles of mutual consent, justice, and the protection of the weaker party. The findings show that klausula baku in contracts, when imposed without mutual agreement, violates Islamic principles of fairness and equity. Islamic law emphasizes justice, transparency, and the need for mutual consent in transactions. The study highlights that such practices, which favor the stronger party, are inconsistent with Sharia-compliant commercial transactions. The research suggests that reforms are necessary to align these contracts with Islamic ethical standards, ensuring that transactions remain just, transparent, and fair for all parties involved.